Linear circuit analysis - Davis, Artice M., 1943- (Boston : PWS, 1998)
This book is divided into four parts: DC analysis; Time domain analysis; Frequency domain analysis; Selected topics.
Keywords: Electric circuit analysis; Electric circuits, Linear; Electric circuit analysis